Maneras de Hacer Mapas - Perán, Martí (2013)
Resumen Entendiendo la cartografía como un modelo dentro de la lógica de la representación. Esta conferencia plantea, en el marco de la crisis de la representación, es decir, de la crisis de la cartografía tradicional, la necesidad de refundar la cartografía. La tarea de devenir cartógrafos supone volver a deducir el valor del territorio y las maneras de discurrir con él, a partir de la experiencia. Esta es la transcripción de la ponencia inédita que el autor presentó el 20 marzo de 2013 en la Escuela de Arquitectura de la Universidad de Costa Rica. Abstract Understanding cartography as a model within the logic of representation. This lecture considers, in the context of the crisis of representation, (that is to say, in the context of the crisis of traditional cartography) the need to establish a fresh foundation for cartography. The task of becoming cartographers implies a return to the possibility of deducing the value of territory and the ways of establishing a discourse with it, on the basis of experience. This is the transcription of the unpublished lecture the author presented on March 20, 2013, at the School of Architecture in the University of Costa Rica.